Tidal dynamics and mangrove carbon sequestration during the Oligo–Miocene in the South China Sea - Daniel S. Collins (Nature Portfolio, 2017)
Mangroves are important carbon-rich biomes, but their long-term impact on the global carbon cycle is relatively unknown. Here, the authors show that the Oligo–Miocene mangroves in the South China Sea stored in excess of 4,000 Gt, demonstrating the long-term impact of mangroves on carbon storage.